Geologically constrained evolutionary geomechanical modelling of diapir and basin evolution: A case study from the Tarfaya basin, West African coast. (24th March 2021) - Hooghvorst, Jean Joseph; Nikolinakou, Maria A.; Harrold, Toby W. D.; Fernandez, Oscar; Flemings, Peter B.; Marcuello, Alejandro
Abstract: We systematically incorporate burial history, sea floor geometry and tectonic loads from a sequential kinematic restoration model into a 2D evolutionary geomechanical model that simulates the formation of the Sandia salt diapir, Tarfaya basin, NW African Coast. We use a poro‐elastoplastic description for the sediment behaviour and a viscoplastic description for the salt. Sedimentation is coupled with salt flow and regional shortening to determine the sediment porosity and strength and to capture the interaction between salt and sediments. We find that temporal and spatial variation in sedimentation rate is a key control on the kinematic evolution of the salt system. Incorporation of sedimentation rates from the kinematic restoration at a location east of Sandia leads to a final geomechanical model geometry very similar to that observed in seismic reflection data. We also find that changes in the variation of shortening rates can significantly affect the present‐day stress state above salt. Overall, incorporating kinematic restoration data into evolutionary models provides insights into the key parameters that control the evolution of geologic systems. Furthermore, it enables more realistic evolutionary geomechanical models, which, in turn, provide insights into sediment stress and porosity. Abstract : The present study uses data coming from a sequential kinematic restoration to constrain an evolutionary geomechanical model for the Tarfaya basin. The resulting geomechanical model provides more realistic results that are in accordance with seismic information. Further sensitivity analysis of the evolutionary geomechanical model identifies the sedimentation rates as the key driver for the basin system evolution.